(untitled) (The Agriculturists, 2019)
Cropping systems of Bangladesh are highly diverse and cultivation costs of puddled transplanted rice (PTR) are high. Therefore, an improved system is needed to address the issues, a field experiment was conducted during 2011-2013 to evaluate system intensification with varying degrees of cropping systems and residue retention. Four cropping systems (CSE) namely CSE1: T. boro rice-T. aman rice (control), CSE2: wheat-mungbean-T. aman rice (wheat and mungbean sown using a power tiller-operated seeder (PTOS) with full tillage in a single pass; puddled transplanted aman), CSE3: wheat-mungbean-dry seeded DS aman rice (DSR), and CSE4: wheat-mungbean-DS aman rice (all sown by PTOS with strip tillage) were compared. Two levels of aman rice residue retention (removed; partial retention i.e. 40 cm of standing stubble) were compared in sub plots. Grain yield was significantly higher (by 11%) when wheat was grown after DSR than PTR. Similarly, PTR and DSR (aman rice) produced statistically similar crop yields. Rice residue retention resulted a significantly higher (by 10%) wheat yield and a slightly increased (by 6%) mungbean yield than that of residues removed. The system productivity of CSE4 was significantly higher (by 10%) than CSE1 when averaged of the two years data. Partial aman residue retention gave significantly higher system yield than residue removal (by 0.6 t ha-1). After two years, no effect of CSE or partial aman residue retention was found on soil physical property (bulk density) of the top soil. Therefore, CSE4 along with residue retention would be more effective for sustainable crop production. The Agriculturists 2019; 17(1-2) 14-30